Outbreak of acute diarrhoeal disease attributed to consumption of faecal contaminated water supplied through damaged pipelines in Thiruper, Tiruvallur district, Tamil Nadu, India, 2016 - Mohan Anandan; Saraswathi VS; Polani Rubeshkumar; Manickam Ponnaiah; Prabhakaran Jesudoss; Kolandaswamy Karumanagounder; Manoj Murhekar (Elsevier, 2021)
Background: On December 24, 2016, 18 Acute Diarrhoeal Disease (ADD) cases were reported in Thiruper village. We aimed to identify potential exposure and propose recommendations. Methods: We defined a case of ADD as occurrence loose stools (≥3 episodes), December 14-30, 2016. We did door-to-door case search, calculated attack rate by age and gender, drew epidemic curve and plotted cases by residence. We conducted a matched case-control study and computed Matched Odds ratio (MOR), 95% confidence interval (95% CI) and Population Attributable Risk (PAR). We collected stool and water specimens for laboratory testing. Results: We identified 38 (6%) cases among 625 residents. The attack rate of ADD was higher among aged <5 years (16.5%), and female (6.8%). The outbreak lasted between 14-27 December 2016 with multiple peaks. Cases clustered in areas receiving water from damaged pipelines crossing open-defecation area. We compared 38 ADD cases with 76 age, gender and neighbourhood matched controls for different exposures. Consuming water supplied through the damaged subterranean pipeline (MOR = 3.7; 95% CI = 1.1 to 16.4; PAR = 72%) was associated with ADD. The environmental investigation pointed out potential faecal contamination of water through damaged subterranean pipelines near open-air defaecation area of village. The collected stool specimens were negative for pathogens, and water specimens tested positive for Escherichia coli. Conclusions: We confirmed that the outbreak of ADD in Thiruper village was due to consumption of water contaminated with E. coli supplied through damaged subterranean pipelines post-cyclone. We recommended the replacement of subterranean pipelines and distribution of chlorinated water.